Pengaruh Atribut Produk Terhadap Keputusan Pembelian (Study Kasus Pada Pengguna Produk Johnson’s Baby Di Desa Rantau Kasai Kecamatan Lintang Kanan Kabupaten Empat Lawang) - Zulaiha Zulaiha; Laili Dimyati (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study aims to determine whether there is influence of product attributes on purchasing decisions. This study uses associative research with a quantitative approach. There are two variables used in this study, namely Product Attributes (X) and Purchase Decision (Y). The sample used in this study was 75 respondents using simple linear statistical analysis techniques and saturated sampling techniques. Sampling was carried out on respondents who used Johnson's Baby products. The results of the simple linear regression analysis test in this study indicate that product attributes have a positive effect on purchasing decisions. It can be seen from the results of simple regression analysis, namely: Y = 18,658 + 0,711 where the constant value is 18,658. The value of the product attribute regression coefficient has a positive influence, which means that if the product attribute increases by one unit, then the purchase decision will increase by 0.711 units. Product attributes have a significant effect on the decision to purchase Johnson's Baby products in Rantau Kasai Village.